Modeling and optimization of photo-Fenton degradation of 2,4-D using ferrioxalate complex and response surface methodology (RSM) - Schenone, Agustina Violeta (2015)
This study reports the application of the photo-Fenton process for the degradation of the herbicide 2,4-dichlorophenoxyacetic (2,4-D). The objective of this research was the evaluation of the procedure at natural pH (pH = 5) using the ferrioxalate complex as iron source at two incident irradiation levels. For this purpose, different combinations of attenuation filters from a solar simulator were tested. Since the process depends on several parameters, the influence of the temperature (T) and peroxide to 2,4-D initial concentration ratio (R) were investigated and optimized by the application of a three-level factorial experimental design combined with the Response Surface Methodology (RSM). The significance of models and their coefficients were assessed with the analysis of variance (ANOVA). The found optimal conditions were: T = 50 °C and R = 46.3 and T = 41.53 °C and R = 41.46, achieving experimental conversions of 91.4 and 95.9% for the low and high radiation levels, respectively. The obtained results are very close to the values predicted by the quadratic models (93.8 and 100.0%). It was concluded that temperature and hydrogen peroxyde concentration have different influences on the response factor depending on the incident irradiation level. It was demonstrated that RSM is a good tool for studying the effects of different variables and their interactions on 2,4-D conversion percentage in the photo-Fenton process. In addition, solution acute toxicity was also evaluated during the treatments under optimum conditions, since some degradation by-products of 2,4-D can be more toxic than the parent compound. For this purpose, the commonly used Microtox® test based on the bacteria Vibrio fischeri was employed.